2020
DOI: 10.3390/cells9102314
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for Sensing and Responding to Hydrogen Peroxide at the Endoplasmic Reticulum

Abstract: The endoplasmic reticulum (ER) has emerged as a source of hydrogen peroxide (H2O2) and a hub for peroxide-based signaling events. Here we outline cellular sources of ER-localized peroxide, including sources within and near the ER. Focusing on three ER-localized proteins—the molecular chaperone BiP, the transmembrane stress-sensor IRE1, and the calcium pump SERCA2—we discuss how post-translational modification of protein cysteines by H2O2 can alter ER activities. We review how changed activities for these three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 148 publications
(238 reference statements)
0
9
0
Order By: Relevance
“…Since the increased unfolded S protein in the ER would trigger the unfolded protein response (UPR), the UPR marker proteins BiP/GRP78, XBP1, and p-eIF2α were examined in RNA transfected HEK293 cells 48 h after transfection ( 23 25 ). The results showed that BiP/GRP78 and XBP1 were up-regulated, and the level of p-eIF2α was higher in S-(deg-S2) and S-(S2-1194) transfected cells than that of the WT and S-(deg-RBD) groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the increased unfolded S protein in the ER would trigger the unfolded protein response (UPR), the UPR marker proteins BiP/GRP78, XBP1, and p-eIF2α were examined in RNA transfected HEK293 cells 48 h after transfection ( 23 25 ). The results showed that BiP/GRP78 and XBP1 were up-regulated, and the level of p-eIF2α was higher in S-(deg-S2) and S-(S2-1194) transfected cells than that of the WT and S-(deg-RBD) groups ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As recently reviewed in [ 26 ], SERCA2B is the main responsible for ER Ca 2+ refilling in vascular endothelium. SERCA2 presents a cysteine residue in the cytosolic P-domain (Cys674) and a pair of cysteine thiols (Cys875 and Cys887) in the longest intralumenal loop 4 (L4) [ 159 ]. It has been shown that S-glutathionylation of Cys674 increases SERCA2B Ca 2+ pumping activity in the cardiovascular system [ 160 , 161 ].…”
Section: Ros Evoke or Modulate Intracellular Ca 2+ Release In Endothelial Cellsmentioning
confidence: 99%
“…Reactive oxygen species (ROS), mainly including singlet oxygen ( 1 O2), superoxide anion (O2 .− ), hydrogen peroxide (H2O2), and hydroxyl radical (HO• ), are produced endogenously as by-products of cellular metabolism primarily in the mitochondria, and serve as indispensable messengers involving in multiple physiological processes. [1][2][3][4][5][6] H2O2, as a kind of representative ROS, has received growing concern by the virtue of its oxidative damage of biomacromolecules such as proteins, liposomes and DNA when overproduced or excessively accumulated . Increasing evidence indicates that the unbalance of H2O2 homeostasis is related to various human diseases including cancers, the Alzheimer's disease, diabetes, and aging.…”
Section: Introductionmentioning
confidence: 99%